Synthesis and characterization of 1,2,3,4-naphthalene and anthracene diimides - Bass, Adam D.; Castellanos, Daniela; Calicdan, Xavier A.; Cao, Dennis D. (Beilstein Journal of Organic Chemistry, 2024)
We report the synthesis and characterization of naphthalene and anthracene scaffolds end-capped by cyclic imides. The solid-state structures of the N-phenyl derivatives, determined by X-ray crystallography, reveal changes in packing preference based on the number of aromatic rings in the core. The optical and electronic properties of the title compounds compare favorably with other previously described isomers and expand the toolbox of electron-deficient aromatic compounds available to organic materials chemists.
Keywords: electron acceptors; organic materials; polycyclic aromatic hydrocarbons